2010
DOI: 10.1177/0011000009359204
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Role of Attachment and Efficacy in Life Satisfaction

Abstract: The study examined interrelationships between attachment, social self-efficacy, career decision-making self-efficacy, and life satisfaction. Social cognitive career theory and attachment theory were integrated to provide a framework for this study. A conceptual model was proposed and tested to determine if social self-efficacy and career decision self-efficacy were full or partial mediators between attachment and life satisfaction. Structural equation modeling methods were utilized to test the model. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 56 publications
(114 reference statements)
4
71
1
4
Order By: Relevance
“…Despite some past studies (e.g., Meng et al 2014;Suldo and Shaffer 2007;Vecchio et al 2007;Wright and Perrone 2010) indicating positive contributions of social selfefficacy to adolescent LS, this study did not find support for social self-efficacy as a unique mediator in the relationship between parental involvement and adolescent LS. Joint consideration of this result and the significant mediation role of social self-efficacy in the relationship between parental involvement and adolescent PA suggests that perceived competency in peer relations may contribute to adolescents' pleasant emotions but may not necessarily affect overall LS like perceived competency in the academic domain.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite some past studies (e.g., Meng et al 2014;Suldo and Shaffer 2007;Vecchio et al 2007;Wright and Perrone 2010) indicating positive contributions of social selfefficacy to adolescent LS, this study did not find support for social self-efficacy as a unique mediator in the relationship between parental involvement and adolescent LS. Joint consideration of this result and the significant mediation role of social self-efficacy in the relationship between parental involvement and adolescent PA suggests that perceived competency in peer relations may contribute to adolescents' pleasant emotions but may not necessarily affect overall LS like perceived competency in the academic domain.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with research that has connected the two variables. For example, Wright and Perrone () found a positive relationship between CDSE and life satisfaction in an ethnically diverse sample. Other scholars have found that college students who had made career decisions were less depressed than their peers who had not (Rottinghaus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, parental attachment and peer attachment have been positively associated with college students' belief in their scholastic competence (Fass & Tubman, ) and career decision self‐efficacy. In a structural analytic study with college students, attachment was found to have a moderate positive effect on career decision self‐efficacy (Wright & Perrone, ), which further demonstrates the influence of attachment on self‐efficacy. Thus, the more securely attached individuals were, the more confident they were in their academic and career decisions.…”
Section: Attachment To Self‐efficacymentioning
confidence: 90%
“…The second hypothesized model, or alternative model, was constructed by adding direct paths from attachment to academic self‐efficacy and career decision self‐efficacy to determine if only a partially mediational model existed; prior research supported this direct effect. In the alternative model, we hypothesized that attachment would also operate as a key source for academic self‐efficacy (Fass & Tubman, ) and career decision self‐efficacy (Wright & Perrone, ).…”
Section: Purpose Of the Studymentioning
confidence: 99%